2013
DOI: 10.1016/j.compind.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Process-oriented tolerancing using the extended stream of variation model

Abstract: Current works on process-oriented tolerancing for multi-station manufacturing processes (MMPs) have been mainly focused on allocating fixture tolerances to ensure part quality specifications at a minimum manufacturing cost. Some works have also included fixture maintenance policies into the tolerance allocation problem since they are related to both manufacturing cost and final part quality. However, there is a lack of incorporation of other factors that lead to increase of manufacturing cost and degrade of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The SoV model mathematically represents the relationship between the feature deviation of the workpiece and the deviation sources (Abellan-Nebot et al , 2013a, 2013b). And the impact of the error sources on the deviations of newly generated features of the part in N-station MMPs can be described as a state space model (Zhou et al , 2003a, 2003b): …”
Section: State Space Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The SoV model mathematically represents the relationship between the feature deviation of the workpiece and the deviation sources (Abellan-Nebot et al , 2013a, 2013b). And the impact of the error sources on the deviations of newly generated features of the part in N-station MMPs can be described as a state space model (Zhou et al , 2003a, 2003b): …”
Section: State Space Modelmentioning
confidence: 99%
“…Compared with the conventional SoV model without considering the machining-induced variations, there is approximate 33 per cent improvement on an average on the quality prediction of the extended SoV model (Abellan-Nebot et al , 2012). The SoV models have been applied in many fields, such as process monitoring (Djurdjanovic and Ni, 2003; Du et al , 2015a, 2015b), fault diagnosis (Zhou et al , 2003a, 2003b), quality-assured setup planning (Liu et al , 2009) and process-oriented tolerancing (Abellan-Nebot et al , 2013a, 2013b). More detailed descriptions of existing research work on SoV model and/or the corresponding applications can be found in review (Ceglarek et al , 2004; Shi and Zhou, 2009; Abellan-Nebot et al , 2013a, 2013b; Yang et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, variation propagation modelling in multistage manufacturing processes has been actively researched. A significant contribution has been made in the directions of part quality prediction [1][2][3][4], variation source identification [5,6], variation compensation [7,8], and process-oriented tolerancing [9] in multistage manufacturing processes. These contributions are often studied under the concept of stream of variation (SoV) and model of a manufactured part [10].…”
Section: Introductionmentioning
confidence: 99%
“…SoV is widely used in multistage complex manufacturing systems to control and improve product quality [ 23 , 24 ]. Abella’n-Nebot et al [ 25 ] proposed an extended SoV model on the basis of process tolerances, which clarify the effects of variables in the machining process on the costs of the manufacturing system and product quality. Zhang et al [ 26 ] constructed a state space model to characterize the relationship between the source variation and the final assembly variation considering the part manufacturing error, fixture position error, and relocation-induced error.…”
Section: Introductionmentioning
confidence: 99%